Policy Management to Develop Tourism Work Culture Consciousness and Increasing Visiting People’s Satisfaction - FRINALDI, ALDRI (Universitas Muhammadiyah Yogyakarta, 2019)
The purpose of this study was to analyze the influence of tourism consciousness work culture by apparatus on visitor’s satisfaction. The research has been done for two consecutive years. The research uses quantitative methods in year 2017, and is continued with a qualitative methods in 2018 . The sampling technique is done by purposive sampling. The findings of the descriptive analysis in general show that all elements of the work culture aware of tourism are categorized sufficient, but there are high categories. Then, the results of multiple regression tests influence the variables of work culture on visitor satisfaction have a significant effect. This is in line with the results in a qualitative manner in general, the visiting community expects an increase in the work culture of tourism awareness among the apparatus and the tourism community to increase community satisfaction visiting the location.